2021
DOI: 10.1038/s41598-021-84136-6
|View full text |Cite
|
Sign up to set email alerts
|

Choriocapillaris microvasculature dysfunction in systemic hypertension

Abstract: We examined the choriocapillaris microvasculature using a non-invasive swept-source optical coherence tomography angiography (SS-OCTA) in 41 healthy controls and 71 hypertensive patients and determined possible correlations with BP and renal parameters. BP levels, serum creatinine and urine microalbumin/creatinine ratio (MCR) specimens were collected. The estimated glomerular filtration rate (eGFR) was calculated based on CKD-EPI Creatinine Equation. The main outcome was choriocapillaris flow deficits (CFD) me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…In this meta-analysis, the data (6,7,(19)(20)(21)(22)(23)(24)(25)(26)(27) shows that systemic hypertension is associated with reduction of vascular density in the superficial capillary plexus (SVD and FAZ area) and deep capillary plexus (DVD) at the macula (Figure 2). This outcome suggests the potential of OCTA technology to serve as tool for pre-clinical retinal microvascular changes in systemic hypertension, where changes in the small retinal vessels may potentially be imaging biomarkers to risk stratify hypertensive complications in end-organs such as the brain, heart, and kidney (28).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In this meta-analysis, the data (6,7,(19)(20)(21)(22)(23)(24)(25)(26)(27) shows that systemic hypertension is associated with reduction of vascular density in the superficial capillary plexus (SVD and FAZ area) and deep capillary plexus (DVD) at the macula (Figure 2). This outcome suggests the potential of OCTA technology to serve as tool for pre-clinical retinal microvascular changes in systemic hypertension, where changes in the small retinal vessels may potentially be imaging biomarkers to risk stratify hypertensive complications in end-organs such as the brain, heart, and kidney (28).…”
Section: Discussionmentioning
confidence: 93%
“…For the optic nerve head, five studies analyzed peripapillary vessel density ( 6 , 20 , 23 25 ), two analyzed inside disc perfusion density ( 20 , 25 ), one analyzed vessel caliber ( 19 ), and one analyzed vessel density (length) ( 23 ). For the choriocapillaris, two studies analyzed density of flow deficits ( 21 , 22 ), two analyzed size of flow deficits ( 21 , 22 ), and two analyzed number of flow deficits ( 21 , 22 ). Nine studies used spectral domain OCTA (SD-OCTA) devices, while two used swept source OCTA (SS-OCTA).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…57,58 This could also apply to AHT, since it has been shown that AHT, especially when poorly controlled, has a detrimental effect on the choriocapillaris. 59 The magnitude of this effect is unknown, but it should be able to counteract opposing forces that would tend to reduce VO2, at least theoretically, such as reduced mean circulation time, shunting of flow, and deep capillary rarefaction. 60,61 Secondly, experimental evidence and mathematical models support that, in the presence of increased O2 availability, the O2 consumption of the inner retina (especially that of the inner and outer plexiform layers) increases, a mechanism that helps to keep inner retinal O2 levels relatively stable.…”
Section: Oxygen Extraction (Vo2)mentioning
confidence: 99%